(untitled) (Actualizaciones en Sida e Infectología, 2025)
Thomas Cleary, in his introduction to Sun Tzu’s Art of War, tells the story of a famous physician, member of a reputed family of healers, who explained that his older brother was able to anticipate and avoid illness, his middle brother diagnosed and treated it early, while he only soothed the pain. The paradox was that the older brother was unknown, the middle brother was poor, while the doctor in the story was the favorite of the noble and powerful. Two key findings from the Sociology of Health help explain this paradox. First, we value our health more when we begin to lose it. Second, our health always concerns us in the first person; we find it difficult to think of health in the plural. If this logic is difficult to understand at the micro level, it is to be expected that the same will be true at the macro level. Do we value an agency focused on preventing disease? Wouldn’t one that prioritized the provision of technologies receive more approval? Based on a counterfactual analysis, we have identified ten consequences for global health if the World Health Organization did not exist. Human smallpox would not have been eradicated Since 1967, WHO has coordinated the campaign against this disease, achieving a unified response to which each country has committed resources. It implemented a strategy of “ring vaccination” and intensive surveillance, rapidly identifying cases and preventing further outbreaks. It played a key role in the distribution and improvement of the vaccine, ensuring that it was available in sufficient quantities and coordinating its distribution. In 1980, WHO officially declared the eradication of smallpox. It was the first human disease to be eradicated. Measles would continue to be a highly-prevalent disease Since the 1970s, the WHO has been advocating that governments include measles vaccination in their national immunization programs, with an emphasis on children, as well as mass campaigns in remote areas. In 2012, WHO set a global goal of reducing measles deaths by 95 % compared to 2000, and although progress has been uneven across regions, this goal has guided many of the global efforts to eradicate the disease. In 2016, the Americas region was the first in the world to be certified as measles-free, marking an important milestone in global efforts to eradicate the disease. Primary health care (PHC) would not have been consolidated With the Declaration of Alma-Ata (1978), the WHO provided an overall vision for the direction of global health. If WHO had not existed, it is very likely that countries would have been seduced by the siren songs of high complexity. In many low- and middle-income countries, the vast majority of people would continue to lack access to basic services while healthcare costs would skyrocket. Essential public health functions (EPHFs) would not have been promoted Since the 1990s, the WHO has conceptualized, standardized and promoted a set of essential functions guiding health systems to provide effective health care, prevent disease and promote health. Since then, it has worked to strengthen national capacities to implement EPHFs through technical assistance, training and by providing guidelines, tools and frameworks so that countries can apply them effectively, while adapting them to their specific contexts. Health surveillance would not have been developed Health surveillance is the most important pillar of public health and deserves to be highlighted among EPHFs, as it enables the detection and monitoring of the emergence of diseases, epidemic outbreaks and other health problems that may affect the population. WHO has been responsible for developing and consolidating health surveillance at global level. As a result, it fostered the improvement of the global capacity to detect, prevent and control disease outbreaks and other public health problems. Thanks to WHO’s efforts, health surveillance has provided a rapid and effective response to health crises. Ministries of health would be less effective WHO has influenced the structure, functioning and policies of ministries of health, guiding countries towards the implementation of key principles to optimize results and providing technical and regulatory advice for the design of national health policies. By assuming a regulatory role, it also contributed to strengthening institutional capacities, ensuring that government health structures are well equipped for effective management. Top of Form The world would experience an endemic infodemic Another relevant contribution of the WHO is global health education, offering clear and reliable information on topics such as vaccination, hygiene, non-communicable diseases and mental health. Without this organization, misinformation and confusion around public health would likely increase. Medications would be more hazardous and less accessible WHO works to ensure access to essential medicines, vaccines and treatments worldwide. Through its programs, such as the Global Immunization Program, the organization has facilitated access to treatment and vaccines in countries with limited resources. Without the WHO, distribution of essential medicines and vaccines to vulnerable populations would be more difficult, especially in low-income countries. It also influences the strengthening of health and essential medicine regulation, by establishing safety and quality standards. Without its contribution, there could be millions of intoxication cases and misuse of public resources. There would be a lack of coordination in the face of pandemics WHO is the lead organization for the coordination of global responses to health emergencies. Although WHO does not formulate binding recommendations that are mandatory for countries to comply with, it suggests the adoption of response measures based on the available scientific evidence. Without the WHO, there would be no effective global platform to monitor and respond to infectious disease outbreaks or pandemics. Probably the Ebola outbreak in 2014, the H1N1 pandemic in 2009 and COVID-19 would have wreaked even more havoc. Without the WHO, the emergency response capacity would be more disorganized, which could lead to a greater spread of disease and thus more deaths. Bottom of Form Equity in health would not be considered in public policies Building and establishing a vision such as universal health coverage (UHC) has been critical to building health equity. In this sense, health is more equally distributed in the world than income: for example, the gap between the country with the longest life expectancy and the country with the shortest is 32 years (61 %), while the gap in GDP per capita is 153,000 %. This highlights the importance of trying to promote policies and strategies to achieve better health equity. This counterfactual analysis exercise allows us to conclude that, after 77 years of WHO’s operation, if it had not existed: a) the world would face greater health risks, b) the burden of disease would be much more concentrated geographically and socially, and c) producing health would be more difficult and more expensive.